Generalized Q Models for Investment - Galeotti, Marzio; Schiantarelli, Fabio (The Review of Economics and Statistics, 1991)
The authors extend the Q theory of investment to allow for adjustment costs for labor, under the additional assumption that the firm is a monopolistic competitor in the output market. The issue of nonconstant returns to scale is also discussed. The authors show that the standard Q model is a special case of a more general model involving testable parameter restrictions. Estimates for the U.S. manufacturing sector suggest that the departure from the assumption of perfect competition and lack of adjustment costs for labor receive empirical support in the data. Copyright 1991 by MIT Press.